Analisis Pemeliharaan Gedung Pada PT. XYZ - Mauludin, Mohammad Fikri; Wolor, Christian Wiradendi; Marsofiyati, Marsofiyati (Universitas Labuhanbatu, 2023)
This research uses a qualitative descriptive approach, namely by describing and analyzing the problems found. Qualitative research is based on primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews and documentation, while secondary data was obtained through books, previous research and articles related to the research. The purpose of this research is to determine building maintenance at PT XYZ which includes maintenance scheduling as well as building conditions and solutions for carrying out building maintenance. From the results of this research, it can be seen that PT XYZ has carried out routine and periodic maintenance, however due to a reduction in employees, maintenance has decreased. This can be seen from the lack of maintenance of storage warehouses, employee work spaces and toilets.